History and current status of publishing processes in Pamplona, ​​​​Colombia - Hoyos Contreras, Sergio Alexander; Niño Prato, Edgar Allan; Durán Jaimes, Andrea Del Pilar; Mojica Acevedo, Eliana Caterine (2025)
The publishing history of Pamplona, ​​Norte de Santander, has been forged by religion, judicial documents, literary works, and journalistic records, which in turn constructed the memory of a town of great historical, geographical, and educational importance.This book seeks to bring together the origin, transformation, and current state of the publishing processes that not only shaped the memory of Pamplona, ​​but also, alongside writing, contributed to the economic activity of several families, fostering typography, lithographs, and the introduction of new printing methods based on technological advances. The research focused on consulting documentary sources, historical archives, and searching for key figures who, through oral accounts, allowed the team to establish a timeline, also integrating the preponderant role of the University of Pamplona from its beginnings to the present, with the Publishing, Publications, and Educational Media Unit and, now, the Publishing House. It is also a tribute to the city that, as mentioned in its review, is the epicenter of publishing production in Norte de Santander.
Keywords: Publisher; Pamplona; typography; lithography; printing